Plasma Β-Endorphin and Cortisol Profiles around Periparturient Period at Stressful Conditions in Egyptian Buffalo - Ha El-Hady Abed; O M El-Malky; Reem S Mourad; I S Al-Gezery (Jurnal Ilmu Ternak dan Veteriner, 2019)
The study determined the level of plasma β-endorphin and cortisol concentrations in peripheral blood circulation of buffalo cows suffering from reproductive disorders (dystocia and retained placenta) and weakness body condition score during periparturient period. Twenty multi-parous Egyptian buffalo cows at late pregnancy period were used for two months before parturition. β-endorphin concentrations were higher in buffalo suffering from reproductive disorders groups. Whereas, β-endorphin concentrations were 134.9±4.8 for retained placenta, 121.3±4.9 for dystocia, 114.2±8.4 for weakness and 113.5±6.5 pg/ml for control. In the closer period around parturition both of plasma β-endorphin and cortisol followed the same trend toward a gradually increased values during -2,-1days and zero time in all groups. A concomitant trend was noticed in β-endorphin and cortisol concentrations in postpartum period with reduce values were observed in all groups after parturition continued for month or more. Buffalo suffering from reproductive disorders were showed a high relative values in β-endorphin and cortisol concentrations. A significant differences (P<0.01) were observed between the experimental groups. Generally, buffaloes suffering reproductive disorders had a clear impact on blood plasma β-endorphin concentration around parturition process.The aim of this study was to determine the relationship between various reproductive disorders as a stress factors with plasma β–endorphin and cortisol in buffalo cows around parturition and changes in these parameters could be used as an objective measure of the stress associated labour. Stress has been hypothesized to be a cause of impaired reproductive efficiency. Stress may cause an overproduction of beta-endorphins and free radicals